2018
DOI: 10.2174/1381612824666171227220815
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiogenesis in Coronary Artery Disease: A Double-Edged Sword: Intraplaque Angiogenesis in Physiopathology and Therapeutic Angiogenesis for Treatment

Abstract: Angiogenesis is described as a sprouting and growth process of new blood vessels from pre-existing vasculature. The relationship between angiogenesis and coronary artery disease (CAD) is double-sided. On one hand, angiogenesis within plaques is responsible for facilitating the growth and vulnerability of plaques by causing intraplaque hemorrhage and inflammatory cell influx, and overabundance of erythrocytes and inflammatory cells within a plaque probably causes plaque rupture, further leading to acute coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Vascular endothelial growth factor (VEGF) is a recognized growth factor playing pivotal roles in angiogenesis through increasing the proliferation rate and activities of endothelial progenitor cells (EPCs) (Yancopoulos et al, 2000;Jin et al, 2015). Angiogenesis could effectively relieve atherosclerotic diseases including CAD (Camare et al, 2017;Wu et al, 2018;Ma Q. et al, 2020), while endothelial cell injury and endothelial dysfunction impair angiogenesis (Xing et al, 2017;Ungvari et al, 2018). Numerous studies have demonstrated that VEGF could attenuate endothelial cell injury or endothelial dysfunction to relieve the pathogenesis of patients with CAD (Jin et al, 2015;Longchamp et al, 2018;Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a recognized growth factor playing pivotal roles in angiogenesis through increasing the proliferation rate and activities of endothelial progenitor cells (EPCs) (Yancopoulos et al, 2000;Jin et al, 2015). Angiogenesis could effectively relieve atherosclerotic diseases including CAD (Camare et al, 2017;Wu et al, 2018;Ma Q. et al, 2020), while endothelial cell injury and endothelial dysfunction impair angiogenesis (Xing et al, 2017;Ungvari et al, 2018). Numerous studies have demonstrated that VEGF could attenuate endothelial cell injury or endothelial dysfunction to relieve the pathogenesis of patients with CAD (Jin et al, 2015;Longchamp et al, 2018;Liang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that low concentrations of ox-LDL promote angiogenesis in human endothelial cells, thus leading to plaque vulnerability and intravascular thrombosis [710]. Therefore, the inhibition of angiogenesis has been considered as a potential therapeutic target in atherosclerosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between angiogenesis and CAD is double-sided [ 4 ]; balancing the contradictory angiogenesis effects might facilitate drug efficacy in CAD. Chinese herbal medicines have an advantage over regulating the balance of the body in different pathological states.…”
Section: Discussionmentioning
confidence: 99%
“…Improving blood flow to the ischemic myocardium plays a critical role in the treatment of CAD, and angiogenesis is an important and promising means of increasing blood flow [ 12 ]. Numerous studies have shown that promoting angiogenesis therapy can improve myocardial ischemia by stimulating formation of collateral networks and increasing blood supply [ 4 , 13 ]. Nox4 alleviated hypoxia/reoxygenation injury by inhibiting apoptosis and promoting angiogenesis via upregulation of HIF-1/VEGF signaling pathway [ 14 ].…”
Section: The Dual Role Of Angiogenesis In Cadmentioning
confidence: 99%
See 1 more Smart Citation